Marketing Public Relations (MPR) Sebagai Strategi Komunikasi Pemasaran OH!Some Dalam Membangun Citra Dan Loyalitas Konsumen - Fauziah Yanis; Galuh Sukmaranti; Muhammad Junaid Kamarudin (PRoMEDIA, 2026)
The development of the retail and lifestyle industry in Indonesia encourages companies to implement effective marketing communication strategies to maintain competitiveness. One of the rapidly growing brands is OH! Some, which carries the concept of retail lifestyle by offering various products for daily needs, beauty, accessories, and entertainment products targeting the younger generation. This study aims to analyze the role of Marketing Public Relations (MPR) as a marketing communication strategy in building a company's image and consumer loyalty. The research method used is a library research study with a qualitative descriptive approach through the analysis of various literature, journals, and relevant scientific sources. The results of the study show that MPR activities through social media, promotional events, influencer collaborations, digital publications, and customer engagement programs can increase brand awareness, strengthen the company's positive image, and encourage consumer loyalty. An integrated communication strategy is an important factor in creating long-term relationships between companies and customers. This is made as an example for writing a journal in PRoMEDIA. The abstract contains a summary of the writing that includes the problem, research methods, and discussion results written briefly and clearly.